Analisis Miskonsepsi Materi Sistem Reproduksi Manusia Menggunakan Instrumen Tiga Tingkat (Three-tier test) Terhadap Mahasiswa Biologi - Eva Muyassaroh; Rosita Widiyaningrum; Zaidah Khoiriyah (Universitas Sains dan Teknologi Komputer, 2024)
The aim of this research is to determine the level of misconceptions of biology students regarding the human reproductive system material. This really needs to be researched because it can find out the extent to which biology students understand the material. To find out the misconceptions experienced by biology students, researchers used the Certainty of Response Index (CRI) method to measure the level of misconceptions biology students had regarding human reproduction material taught by lecturers. This research uses qualitative methods, with descriptive research type. The subjects of this research consisted of all biology students. The population in this study were 36 biology students. The data collection technique uses a questionnaire containing diagnostic questions at the Three Tier Test level with the Certainty of Response Index (CRI) method where in the questions there are three levels of categories, namely questions, reasons and beliefs. This questionnaire is distributed online via Google Form. The data obtained was processed using percentage techniques. The results of this research were analyzed by adjusting the levels of the categories of understanding the concept, not knowing the concept and misconceptions. The results obtained will later show biology students who experience misconceptions and biology students who already understand the concept. The results of this research show that 21.5% of biology students understand the concept, 31.4% do not understand the concept and 25% of biology students experience positive misconceptions, 22.2% negative misconceptions. It can be concluded that it turns out that biology students still experience many misconceptions regarding the human reproductive system material compared to biology students who understand the concept.)